Chronic effects of non‐weathered and weathered crude oil and dispersant associated with the Deepwater Horizon incident on development of larvae of the eastern oyster, Crassostrea virginica. (27th May 2016) - Langdon, Chris J.; Stefansson, Emily S.; Pargee, Suzanne M.; Blunt, Susanna M.; Gage, Susan J.; Stubblefield, William A.
Abstract: The present study examined the effects of chronic exposure of eastern oyster ( Crassostrea virginica ) larvae to the water‐accommodated fractions of fresh and weathered oils collected from the Deepwater Horizon incident, with and without additions of the dispersant Corexit 9500A, as well as to solutions of Corexit alone. Both shell growth of larvae exposed to test materials for a period of 10 d and larval settlement after 28 d of exposure were the most sensitive endpoints, with the 10‐d growth endpoint being less variable among replicates. Growth and settlement endpoints were more sensitive than larval survival and normal development after 10 d and 28 d. Acute‐to‐chronic ratios calculated in the present study suggest that acute toxicities of oils and dispersant for oysters are not predictive of chronic effect levels for growth and settlement; therefore, chronic bioassays are necessary to assess these sublethal effects, in addition to standard 48‐h acute toxicity tests. Comparison of 10% effective concentration (EC10) values for chronic 10‐d growth and 28‐d settlement endpoints with concentrations of total polycyclic aromatic hydrocarbons and dipropylene glycol n‐butyl ether (a marker for Corexit) in seawater samples, collected during and after the Deepwater Horizon incident, indicated it was unlikely that elevated concentrations of water‐soluble fractions of oil and dispersant in the nearshore environment had significant adverse effects on the growth and settlement of eastern oyster larvae. Environ Toxicol Chem 2016;35:2029–2040. © 2016 SETAC